Heart Failure With Preserved Ejection Fraction: Heterogeneous Syndrome, Diverse Preclinical Models. Issue 12 (10th June 2022) - Roh, Jason; Hill, Joseph A.; Singh, Abhilasha; Valero-Muñoz, María; Sam, Flora
Abstract : Heart failure with preserved ejection fraction (HFpEF) represents one of the greatest challenges facing cardiovascular medicine today. Despite being the most common form of heart failure worldwide, there has been limited success in developing therapeutics for this syndrome. This is largely due to our incomplete understanding of the biology driving its systemic pathophysiology and the heterogeneity of clinical phenotypes, which are increasingly being recognized as distinct HFpEF phenogroups. Development of efficacious therapeutics fundamentally relies on robust preclinical models that not only faithfully recapitulate key features of the clinical syndrome but also enable rigorous investigation of putative mechanisms of disease in the context of clinically relevant phenotypes. In this review, we propose a preclinical research strategy that is conceptually grounded in model diversification and aims to better align with our evolving understanding of the heterogeneity of clinical HFpEF. Although heterogeneity is often viewed as a major obstacle in preclinical HFpEF research, we challenge this notion and argue that embracing it may be the key to demystifying its pathobiology. Here, we first provide an overarching guideline for developing HFpEF models through a stepwise approach of comprehensive cardiac and extra-cardiac phenotyping. We then present an overview of currently available models, focused on the 3 leading phenogroups, which are primarily based on aging, cardiometabolic stress, and chronic hypertension. We discuss how well these models reflect their clinically relevant phenogroup and highlight some of the more recent mechanistic insights they are providing into the complex pathophysiology underlying HFpEF.